2008
DOI: 10.1016/j.neuropsychologia.2007.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of spatial orienting towards angry faces: A source localization study

Abstract: The goal of this study was to examine behavioral and electrophysiological correlates of involuntary orienting toward rapidly presented angry faces in non-anxious, healthy adults using a dot-probe task in conjunction with high-density event-related potentials and a distributed source localization technique. Consistent with previous studies, participants showed hypervigilance toward angry faces, as indexed by facilitated response time for validly cued probes following angry faces and an enhanced P1 component. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 75 publications
(114 reference statements)
11
77
2
1
Order By: Relevance
“…The timing of these effects is consistent with the findings reported by the only behavioural study that systematically manipulated the stimulus-onset-asynchrony between distracter and target in order to estimate the time-course of capture effect (Leblanc and Jolicoeur, 2005). Our results are also consistent with electrophysiological evidence of consequences to attentional capture by emotional stimuli (Fox et al, 2008;Pourtois et al, 2004;Santesso et al, 2008). These studies reported that fearful and angry faces capture attention and subsequent targets appearing at the same location showed an enhanced sensory processing at the P1 stage.…”
Section: Discussionsupporting
confidence: 89%
“…The timing of these effects is consistent with the findings reported by the only behavioural study that systematically manipulated the stimulus-onset-asynchrony between distracter and target in order to estimate the time-course of capture effect (Leblanc and Jolicoeur, 2005). Our results are also consistent with electrophysiological evidence of consequences to attentional capture by emotional stimuli (Fox et al, 2008;Pourtois et al, 2004;Santesso et al, 2008). These studies reported that fearful and angry faces capture attention and subsequent targets appearing at the same location showed an enhanced sensory processing at the P1 stage.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, very early ERF modulations by attention (e.g., Poghosyan and Ioannides, 2008;Ioannides and Poghosyan, 2012) and facial expression (e.g., Morel et al, 2009;Bayle and Taylor, 2009) have been reported. While these results are extremely exciting, as they suggest that our brain processes and modulates visual information more quickly than is generally thought, difficulties of replication (e.g., Santesso et al, 2008;Fu et al, 2010b) make it hard to draw conclusions on what mechanisms are at play. One possible reason for such inconsistencies is that experimental paradigms and methods vary widely.…”
Section: Discussionmentioning
confidence: 98%
“…Applying this basic knowledge to the study of threat-related attention biases in anxiety, researchers can now generate specific hypotheses about P1 modulations in anxious versus non-anxious individuals during performance on the classic attention tasks being used in the study of processing biases in anxiety. Finally, although the spatial resolution of ERP measurements is limited, both theoretically and technologically, multichannel recordings allow for a rough estimation of the intracranial sources of the electrical activity recorded on the scalp (Ladouceur et al, 2006;Reynolds and Richards, 2005;Santesso et al, 2008).…”
Section: Event-related Potentials (Erps)mentioning
confidence: 99%